Epidemiology, Diagnosis And Chemoprophylaxis Of Trypanosoma Evansi Infection In Dairy Cattle - Cheah, Tong Soon (1997)

(untitled)
Trypanosomiasis caused by Trypanosoma evansi is considered to be one of the diseases of economic importance affecting dairy cattle in Malaysia. An investigation into the epidemiology, diagnosis and chemoprophylaxis of T. evansi infection in these animals was carried out. F our studies were conducted in this investigation.In the first study, random blood samples were collected from animals of different age/physiological status for parasitological, serological, haematological and biochemical tests between August 1995 and July 1996 The mean prevalence was highest in the lactating animals ( 134 %) followed by those in the dry herd (88%), late pregnant animals (81%), early pregnant animals (47 %), calves (03 %) and yearlings (02%) The mean prevalence was significantly different (p<0.05) between cows and the other groups (calves and yearlings) Among the cows there was significant difference in the mean prevalence between the early pregnant and lactating animals (p<0.05) The association between the prevalence in lactating cows and rain days was significant (p< 0 05) Infected dry cows had a significant decrease in the PCV, Hb and albumin levels (p< 0 05) The antigen-detection ELISA was a useful diagnostic tool for detection of T. evansi infections as it was capable of detecting 9 1 % of trypanosome-positive ammals